ubungan Welas Asih Terhadap Diri Sendiri dengan Citra Tubuh pada Remaja Putri - Bayu Dwisetyo; Sri Tiara Wati Al-Amri (STIKes YARSI Pontianak, 2026)
Background: Adolescence is characterized by physical and psychological changes that can influence body perception. Adolescent girls tend to be more sensitive to their physical appearance, making them more vulnerable to developing a negative body image. One factor that contributes to the development of a positive body image is self-compassion. Objective: This study aimed to examine the relationship between self-compassion and body image among eighth-grade female students at MTs Negeri 1 Bitung. Methods: This study employed a quantitative approach using a descriptive correlational design with a cross-sectional approach. The study population consisted of 115 female students, with a sample of 89 respondents selected through purposive sampling. The research instruments were the Self-Compassion Scale (SCS) and the Indonesian version of the Multidimensional Body-Self Relations Questionnaire–Appearance Scale (MBSRQ-AS). Data were analyzed using the Pearson correlation test. Results: The Pearson correlation test showed a p-value of 0.031 (p<0.05), indicating a statistically significant relationship between self-compassion and body image. Conclusion: There is a positive relationship between self-compassion and body image among eighth-grade female students at MTs Negeri 1 Bitung.